Impact of Melatonin Spraying on Growth and Yield of Some Sesame Varieties - Saad I. Obada, Imad M. Ali (Forest Chemicals Review, 2022)
There is minimal information on the melatonin spraying to different sesame varieties and their effect on growth and yield attributes. The goal of this study was to examine the influence of different doses of melatonin on agronomic parameters and yield of sesame varieties. The experiment was conducted by constructing split plots according to the randomized complete block design (RCBD) and with three replications. four different melatonin concentrations were tested in the main plots, and four different sesame kinds were tested in the sub-plots (Rafidain, Sumer, Wadaa and Had). Plant height, leaf area, capsule number, seed number per capsule, and seed output were all considerably better with 30 mg L-1 melatonin than with 20 mg L-1 dry weight, according to the results of this study. Rafidain variety exhibited highest plant height while recorded the lowest value of 1000 seed weight. Had cultivar was much superior in leaf area. Wadaa variety achieved the greatest rate dry weight, number of capsules per plant, number of seeds per capsule and seed production. Sumer seeds achieved the maximum value of 1000 seed weight while recorded the lowest rate of plant height, leaf area, dry weight, number of capsules per plant, and number of seeds per capsule.